2012
DOI: 10.1258/jms.2012.012080
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Mortality in Mammographic Screening in Europe: A Review of Incidence-Based Mortality Studies

Abstract: Objectives To estimate the impact of service mammography screening on breast cancer mortality using European incidence-based mortality (IBM) studies (or refined mortality studies). IBM studies include only breast cancer deaths occurring in women with breast cancer diagnosed after their first invitation to screening. Methods We conducted a literature review and identified 20 publications based on IBM studies. They were classified according to the method used for estimating the expected breast cancer mortality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 25 publications
6
144
0
5
Order By: Relevance
“…Qualitative MBD assessment was performed by radiologists using the fourth edition BI-RADS scheme on a discrete scale (1)(2)(3)(4). For this study, BI-RADS breast density assessment was performed in two phases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative MBD assessment was performed by radiologists using the fourth edition BI-RADS scheme on a discrete scale (1)(2)(3)(4). For this study, BI-RADS breast density assessment was performed in two phases.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 It has been shown that 30% reduction in breast cancer mortality is partly attributable to improved knowledge of its risk factors and advances in early detection and treatment strategies. 3,4 Breast density refers to the proportion of the breast that is composed of fibroglandular tissue 5 and is related to established breast cancer risk factors such as genetics, hormonal agents and lifestyle characteristics. 6,7 Most importantly, breast density reduction has been shown to be a prognostic marker of response to adjuvant tamoxifen therapy in post-menopausal females.…”
Section: Introductionmentioning
confidence: 99%
“…MMG screening studies were conducted in Australia to reduce mortality from BC (Roder et al, 2008;Morrell et al, 2012). In another study, mortality due to BC was reduced by 26% in patients who were invited to a screening program for BC (Njor et al, 2012). In other related studies, MMG screening resulted in less DB-related mortality (van Schoor et al, 2011;Puliti and Zappa, 2012) and reduced BC by 15% compared to self-and clinical breast examinations in patients aged 39-69 years (Nelson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A relative risk reduction (RRR) in breast cancer mortality of 20% in women invited to screening compared with non-invited control groups was found by a UK panel and Cochrane, both only including RCT-studies in their systematic review [6,9]. Two systematic reviews over incidence based studies estimated a 25–26% RRR [10,11], while a review of quasi-experimental studies found an effect of 16–23%, depending on the type of study design [8]. Consequently, the expected screening effect on breast cancer mortality is attached with uncertainty.…”
Section: Introductionmentioning
confidence: 99%